The Role of Teachers in Realizing Free Learning During Covid 19 Pandemic: (Case Study of Nahdlatul Ulama 2 Gresik Senior High School) - Mauludia, Muhammad Iqbal; Mulyadi, Mulyadi (Journal of Social Science and Economics, 2022)
Teachers are the most important part in the teaching and learning process, in formal, informal, or non-formal education. The Ministry of Education and Culture's breakthrough regarding Freedom of Learning is expected to be able to contribute more to the development of human resources, because quality human resources are assets for the nation to advance various fields, especially in improving the quality of education. The COVID-19 pandemic has had a major impact on the world of education, which makes it obligatory to do online learning. The objectives of this study are as follows: a) to find out the role of teachers in realizing independent learning for students during the covid-19 pandemic at SMA NU 2 Gresik, b) to find out what are the obstacles faced by teachers in realizing independent learning during the covid-19 pandemic. at SMA NU 2 Gresik. This research uses qualitative research methods with a case study approach. The results of this study indicate that the teacher's role in realizing independent learning is: a) Preparing for independent learning, b) Implementing independent learning and c) Evaluation of independent learning. The obstacles in realizing independent learning are divided into two, namely internal and external constraints. Internal constraints include: a) Not being able to monitor students directly, b) Teachers lack of technology mastery, c) Lack of maximum inculcation of character values.